Jelly candy enriched with BRS Violeta grape juice: Anthocyanin retention and sensory evaluation - Nishiyama-Hortense, Yara Paula de Oliveira [UNESP]; Rossi, Maria Júlia de Paula [UNESP]; Shimizu-Marin, Victoria Diniz [UNESP]; Janzantti, Natália Soares [UNESP]; Gómez-Alonso, Sergio; Da-Silva, Roberto [UNESP]; Lago-Vanzela, Ellen Silva [UNESP] (Elsevier, 2022)
This study aimed to evaluate the applicability of grape juice, despite being from immature grape, as a bioingredient and natural coloring in jelly candy. The product was made containing BRS Violeta grape juice, gelatin, honey, agar and natural aroma. The qualitative and quantitative composition of anthocyanins present in the grapes, the juice produced, and the juice-containing jelly candy were determined using HPLC-DAD- ESI -MS/MSn; and, sensory analysis methods (acceptance and Rate-All-That-Apply (RATA)) were used to assess the quality of the candy produced. The product had a concentration of total anthocyanins (mg malvidin-3,5-glucoside·kg fruit−1) of 686.78, with a retention of 41% in relation to the concentration determined in the juice. However, compared to the grape, the concentration of diglycosylated anthocyanins, including the coumarylated ones, increased because they are more stable compounds. According to the sensory characterization, the candy presented a satisfactory acceptance; according to the RATA method, it was characterized mainly as purple and uniform in color, shiny and gelatinous in appearance. Finally, it is concluded that the application of juice, combined with the other ingredients of the formulation, resulted in a product pleasant and with the considerable concentration of anthocyanins and, with grape odor and flavor.
Keywords: Anthocyanins; Bioingredients; Enriched candies; Hybrid grapes